2022
DOI: 10.5194/cp-18-1035-2022
|View full text |Cite
|
Sign up to set email alerts
|

Simulated range of mid-Holocene precipitation changes from extended lakes and wetlands over North Africa

Abstract: Abstract. Enhanced summer insolation over North Africa induced a monsoon precipitation increase during the mid-Holocene, about 6000 years ago, and led to a widespread expansion of lakes and wetlands in the present-day Sahara. This expansion of lakes and wetlands is documented in paleoenvironmental sediment records, but the spatially sparse and often discontinuous sediment records provide only a fragmentary picture. Previous simulation studies prescribed either a small lake and wetland extent from reconstructio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 39 publications
5
23
2
Order By: Relevance
“…Our study confirmed that Megalake Chad does not influence the northward monsoon movement when western lakes are missing (Broström et al, 1998;Carrington et al, 2001;Chandan & Peltier, 2020). We also confirmed the influence of Western Sahara lakes on the northward monsoon movement (Specht et al, 2022), but further stressed that Megalake Chad could extend the westerly monsoon eastward when accompanied by Western Sahara lakes. Chandan and Peltier (2020) underestimated the contribution of lakes by supposing that the weakened SHL induced by the surface cooling effect would reduce precipitation.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Our study confirmed that Megalake Chad does not influence the northward monsoon movement when western lakes are missing (Broström et al, 1998;Carrington et al, 2001;Chandan & Peltier, 2020). We also confirmed the influence of Western Sahara lakes on the northward monsoon movement (Specht et al, 2022), but further stressed that Megalake Chad could extend the westerly monsoon eastward when accompanied by Western Sahara lakes. Chandan and Peltier (2020) underestimated the contribution of lakes by supposing that the weakened SHL induced by the surface cooling effect would reduce precipitation.…”
Section: Discussionsupporting
confidence: 82%
“…However, we found that such SHL weakening effect can be offset by the adjacent cyclonic circulation response in the lower atmosphere, which promotes precipitation. Moreover, we found that the northward WAM movement goes with a weakened AEJ and a strengthened TEJ, in agreement with Specht et al (2022). Therefore, we emphasized the importance of how the climate model represents the AEJ and TEJ behaviors in reproducing the MH climate (Claussen et al, 2017;Bercos-Hickey et al, 2020;Ngoungue et al, 2021).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations